Use of Computer-assisted Model in Diagnosis of Drug Hypersensitivity Jaundice. Issue 5869 (30th June 1973) - Stern, R. B.; Maxwell, J. D.; Knill-Jones, R. P.; Thompson, R. P. H.; Williams, Roger
Abstract : Of 374 patients with jaundice seen in the liver unit over a four-year period 21 were finally thought to be hypersensitive to one of seven different drugs. The clinical, laboratory, and histological features were often difficult to distinguish from those of viral hepatitis, tumour of the extrahepatic biliary tree, or primary biliary cirrhosis. A computer-assisted diagnostic model made use of minor differences, and made a correct diagnosis in all patients. Even when information about drug ingestion was left out it was still correct in 81% of patients. Sixty-four other patients gave a history of ingestion of potentially hepatotoxic drugs of whom 62 were correctly diagnosed by the computer. In the complete series of 374 patients only two were incorrectly computed to have drug jaundice when there was no history of drug ingestion. Two additional patients became jaundiced after exposure to drugs, but were found to have primary biliary cirrhosis.